Signaling Elaboration: Combining French Gerund Clauses with Lexical Cohesion Cues - Marianne Vergez-Couret; Clémentine Adam (Discours)
In this paper, we focus on the Elaboration relation and on its automatic identification in French, using the theoretical framework of Segmented Discourse Representation Theory (SDRT). One of the information sources identified by the SDRT framework to infer the Elaboration relation is based on the existence of a potential subsumption link between the eventualities at stake, depending on lexical semantics and world knowledge. We investigate this claim by combining a weak syntactic marker of the Elaboration relation, namely the gerund clause, with lexical cohesion cues. We aim at automatically identifying gerund clauses which are Elaborations by finding cohesive links between the host main clause and the gerund clause. This approach makes it possible to accurately detect few cases of intra-sentential Elaborations in our corpus, confirming the fact that lexical cohesion cues are relevant for this task.